Sex differences in kappa opioid receptor inhibition of latent postoperative pain sensitization in dorsal horn. (February 2020) - Custodio-Patsey, Lilian; Donahue, Renée R.; Fu, Weisi; Lambert, Joshua; Smith, Bret N.; Taylor, Bradley K.
Abstract: Tissue injury produces a delicate balance between latent pain sensitization (LS) and compensatory endogenous opioid receptor analgesia that continues for months, even after re-establishment of normal pain thresholds. To evaluate the contribution of mu (MOR), delta (DOR), and/or kappa (KOR) opioid receptors to the silencing of chronic postoperative pain, we performed plantar incision at the hindpaw, waited 21 days for the resolution of hyperalgesia, and then intrathecally injected subtype-selective ligands. We found that the MOR-selective inhibitor CTOP (1–1000 ng) dose-dependently reinstated mechanical hyperalgesia. Two DOR-selective inhibitors naltrindole (1–10 μg) and TIPP[Ψ] (1–20 μg) reinstated mechanical hyperalgesia, but only at the highest dose that also produced itching, licking, and tail biting. Both the prototypical KOR-selective inhibitors nor-BNI (0.1–10 μg) and the newer KOR inhibitor with more canonical pharmocodynamic effects, LY2456302 (0.1–10 μg), reinstated mechanical hyperalgesia. Furthermore, LY2456302 (10 μg) increased the expression of phosphorylated signal-regulated kinase (pERK), a marker of central sensitization, in dorsal horn neurons but not glia. Sex studies revealed that LY2456302 (0.3 μg) reinstated hyperalgesia and pERK expression to a greater degree in female as compared to male mice. Our results suggest that spinal MOR and KOR, but not DOR, maintain LS within a state of remission to reduce the intensity and duration of postoperative pain, and that endogenous KOR but not MOR analgesia is greater in female mice. Highlights: Surgery produces a long-lasting kappa opioid receptor analgesia. KOR analgesia that prevents the transition from acute to chronic postoperative pain. KOR analgesia is, particularly strong in females.